2010
DOI: 10.1128/jcm.01769-09
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Clinical Characteristics of Staphylococcus lugdunensis Prosthetic Joint Infections

Abstract: Staphylococcus lugdunensis is a coagulase-negative staphylococcus that has several similarities to Staphylococcus aureus. S. lugdunensis is increasingly being recognized as a cause of prosthetic joint infection (PJI). The goal of the present retrospective cohort study was to determine the laboratory and clinical characteristics of S. lugdunensis PJIs seen at the Mayo Clinic in Rochester, MN, between 1 January 1998 and 31 December 2007. Kaplan-Meier survival methods and Wilcoxon sum-rank analysis were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 18 publications
6
51
0
5
Order By: Relevance
“…lugdunensis has been reported as an agent of endovascular infection, particularly in patients with inguinal skin breaks (vasectomy or cardiac catheterization via the femoral route [6,8]) and as a cause of pelvic girdle abscesses (2), highlighting that the predominant ecological niche of the organism is likely to be the groin. S. lugdunensis has also been reported as a cause of skin and soft tissue infections, particularly involving the breast, abdomen, and lower limbs (1,2,4), and has been identified as an agent of prosthetic joint infection (10). In keeping with these reports, studies that have screened healthy persons for carriage have confirmed identification from skin of the abdomen, groin, and lower extremities (3,12).…”
Section: S Lugdunensis Is a Coagulase-negativesupporting
confidence: 55%
See 1 more Smart Citation
“…lugdunensis has been reported as an agent of endovascular infection, particularly in patients with inguinal skin breaks (vasectomy or cardiac catheterization via the femoral route [6,8]) and as a cause of pelvic girdle abscesses (2), highlighting that the predominant ecological niche of the organism is likely to be the groin. S. lugdunensis has also been reported as a cause of skin and soft tissue infections, particularly involving the breast, abdomen, and lower limbs (1,2,4), and has been identified as an agent of prosthetic joint infection (10). In keeping with these reports, studies that have screened healthy persons for carriage have confirmed identification from skin of the abdomen, groin, and lower extremities (3,12).…”
Section: S Lugdunensis Is a Coagulase-negativesupporting
confidence: 55%
“…However, based on the production of bound coagulase (5), S. lugdunensis can also easily be misidentified in the laboratory as S. aureus (8), as was initially the case in this instance. Because it shares certain virulence characteristics with S. aureus, S. lugdunensis is now well recognized as a potential cause of invasive and destructive infections that can mimic S. aureus disease (1,4,7,10,14).…”
Section: S Lugdunensis Is a Coagulase-negativementioning
confidence: 99%
“…Such associations of S. lugdunensis with severe infections were previously reported in various patient cases and series, including specimens from various origins, i.e. endocarditis, skin and soft tissue infections, arthritis, prosthetic joint infections, sepsis without identified gateway, pseudo-toxic shock syndrome, necrotizing sinusitis, and brain abscesses (30)(31)(32)(33)(34)(35). S. lugdunensis is the second cause of endocarditis due to CoNS, with a poor prognosis in 40% of cases (36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the isolate showed negative results for the slide and tube coagulase tests (performed with EDTAhuman plasma) with the primary and subculturing cultures. In the tube coagulase test, the isolate tested negative at every time point (1,2,3,4,6,8,10,12, and 24 h). Staphylococcus aureus (ATCC 25923) was used as the positive control.…”
mentioning
confidence: 99%